Corporate Financial Policies In Malaysia : A Study Of The Industrial And Consumer Products Sectors - Mohamed Ibrahim, Abdul Samad (2003)
This these constitutes a research on the Corporate Financial Policies of Companies in the Industrial and Consumer Products sectors in the KLSE.